1998
DOI: 10.1021/es970181d
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Uranium−Citrate Complexes:  Implications for Extraction of Uranium from Soils

Abstract: Citrate is often used as a complexing agent to mobilize sorbed and precipitated uranium in both in situ and ex situ extraction of soils and nuclear reactor components. The biodegradability of U−citrate complexes is an important control over the potential migration of residual uranium after the extraction process is complete. In solutions buffered at pH 6−7, limited biodegradation of citrate is observed within 10 days with initial U:citrate molar ratios ranging from 1:2 to 1:8; however, over 99% of the citrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 11 publications
0
41
1
Order By: Relevance
“…All results were verified in at least one additional, independent experiment with duplicate cultures. Uranium precipitation, sorption, and speciation are influenced by pH (5,18,49). Therefore, we monitored pH in selected cultures over the course of the U(VI) reduction experiments.…”
Section: Methodsmentioning
confidence: 99%
“…All results were verified in at least one additional, independent experiment with duplicate cultures. Uranium precipitation, sorption, and speciation are influenced by pH (5,18,49). Therefore, we monitored pH in selected cultures over the course of the U(VI) reduction experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Another study by Banaszak et al (1999) suggests that the uranyl-citrate complex itself is toxic to P. fluorescens. Finally, Huang et al (1998) show that there is incomplete citrate (0.55 mmol/L) degradation by a mixed cell culture in the presence of uranyl (0.42 mmol/L) at pH 6. This study shows that uranyl inhibits cell metabolism at low, environmentally relevant concentrations and that the inhibition is associated with the binding of uranyl to the cell envelope.…”
Section: Introductionmentioning
confidence: 90%
“…It is due to lack of transport inside the cell and not to Cd toxicity or inhibition of cell function [7]. To maintain cell electroneutrality, proton was simultaneously transported and metabolized with the negatively charged bidentate [Fe(OH) 2 -citrate] 2− and [Zn-citrate] − [9]. Therefore, with the consumption of proton, pH of 1:1 Fe:citrate and Zn:citrate media gradually increased to the values greater than 7.9 to the end of the experiments.…”
Section: Biodegradation Of Fe(iii)- Zn-and Cd-citrate Complexmentioning
confidence: 99%
“…Huang et al investigated the biotransformation of non-biodegradable U-citrate complex at alkaline pH, they found that over 99% of the citrate was metabolized by bacteria, and speculated that dissociation of citrate from U-citrate complex at alkaline pH raised the bioavailability of citrate [9]. Whereas, for Ni-citrate complex, limited biodegradation of citrate was observed due to the formation of tridentate Ni-citrate complex at alkaline pH [10].…”
Section: Introductionmentioning
confidence: 99%